Economic education and household financial outcomes during the financial crisis - Paul W. Grimes; Kevin E. Rogers; William Bosshardt (Journal of Risk and Financial Management, 2021)
Using cross-sectional data from a nation-wide survey of American head-of-households conducted in the spring of 2010, we examined the ameliorating effects of economic literacy on the probability of specific household financial outcomes resulting from the 2008 financial crisis and the associated Great Recession. A series of probit regressions were estimated to capture the impact of economic literacy on the probability that households experienced job loss, delinquent mortgage payments, delinquent credit card payments, delinquent auto loan payments, loss of home, and personal bankruptcy. The head-of-household's economic literacy was measured by the level of formal education received in economics and by the score achieved on an in-survey quiz of basic economic concepts and principles. The results indicate that realized quiz scores were correlated with the mitigation of job loss, late payment behavior, and personal bankruptcy, ceteris paribus. However, the results for the impact of formal economic coursework in school were mixed.
Keywords: 330; economic literacy; financial crisis; Great Recession; household finances